International trade and financial integration: A weighted network analysis - Giorgio Fagiolo; Javier Reyes; Stefano Schiavo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
In this paper we compare the patterns of trade and financial integration by exploiting network analysis. Our results show that, by combining binary and weighted network analysis, it is possible to deliver more precise and thorough insights on the topological structure and properties of the international trade and financial networks (ITN and IFN). We find that the ITN is more densely connected than the IFN and that the degree of international financial integration varies with asset type. Our results also indicate that richer countries are better linked and form groups of tightly interconnected nodes. This can be seen as a sign of the persistent relevance of local relations. Yet, the growing importance of global links is testified by the disassortative feature of both the ITN and the IFN: poorly connected nodes tend to connect to central ones and use them as hubs to access the rest of the network.
Keywords: F10; F36; F40; G15; 330; International Trade; International Financial Flows; Globalization; Complex Weighted Networks; Dynamics; Globalisierung; Internationale Wirtschaftsbeziehungen; Kapitalmobilität; Internationaler Finanzmarkt; Netzwerk; Theorie; Schätzung; Welt